ASPECTS ABOUT THE PROPERTIES OF A BAINITIC DUALPHASE S.G. CAST IRON - Milosan, Ioan (European Scientific Journal, ESJ, 2014)
The paper presents a study about the influence of some heat treatment parameters of austempering and annealing with tempering over the structure and values of hadness, tensile strength, elongation and impact strength of a low alloyed S.G. cast iron. It is pointed out the influence of some factors (the temperature and the holding time at the isothermal level) on the phase transformation and properties in the studied cast iron.